Differences in the Effect of the Combination of Home-Based Walking Exercise and Pursed Lip Breathing with Pranayama Exercise on Increasing Lung Capacity in COPD Conditions - Nurul Fithriati Haritsah; Yoga Handita Windiastoni; Noerdjannah Noerdjannah (Indonesian Journal of Medicine, 2022)
Background:  Data from the pulmonary disease polyclinic at Bangil Hospital showed an increase in Chronic Obstructive Pulmonary Disease (COPD) patient visits. In 2018 the number of COPD patients who visited the pulmonary disease clinic for the last 3 months was 219 COPD patients. COPD patients experience deficits in caring for themselves due to various symptoms that manifest as a manifestation of the development of COPD disease. This study aimed to determine the differences in the effect of the combination of home-based walking exercise and pursed lip breathing with pranayama exercise on increasing lung capacity in COPD conditions.Subjects and Method:  The design of this study is a two-group pre and post-test design. As many as 8 respondents to the pursed lip breathing intervention and home-based walking exercise and 8 respondents to the pranayama exercise according to the inclusion and exclusion criteria. This study compared the effect of walking exercises combined with pursed lip breathing and pranayama exercise on increasing lung vital capacity in COPD patients. The independent variable is lung capacity. The dependent variable is home-based walking exercise and pursed lip breathing This research was conducted once a week for 12 weeks in May-August 2021 at Dungus Madiun Lung Hospital. All categories were analyzed using a Mann-Whitney run on SPSS.Results:  The results before being given the combination of pursed lip breathing and home-based exercises (Mean= 95.39; SD= 0.70) compared to after being given the combination of pursed lip breathing and home-based exercises (Mean= 98.08; SD= 1.23) and statistically significant p<0.001 increases lung capacity in COPD conditions. The results before being given pranayama exercises (Mean= 95.83; SD= 0.71), after being given pranayama exercises (Mean= 97.54; SD= 0.81) and statistically significant p<0.001 increased lung capacity in COPD conditions. score in the elderly was 32.57 (Mean= 32.57; SD= 4.49).Conclusion:  There is an effect of giving a combination of home-based walking exercises and pursed lip breathing in increasing the lung capacity of COPD patients. There is an effect of providing pranayama exercise in increasing the lung capacity of COPD patients.Keywords: home-based walking exercise, pranayama exercise, pursed lip breathing, lung capacityCorrespondence:  Nurul Fithriati Haritsah. Department of Physiotherapy, Health Polytechnic Surakarta, Ministry of Health. Jl. Letjend Sutoyo, Mojosongo, Jebres, Surakarta 57127, Central Java, Indonesia. Email: nurulfithriati_haritsa@yahoo.com.Indonesian Journal of Medicine (2022), 07(04): 439-448https://doi.org/10.26911/theijmed.2022.07.04.09